مستوى التوافق النفسي لدى التلاميذ ذوي الاحتياجات الخاصة - الهلي, مصباح; قوراح, محمد (جامعة الوادي - University of Eloued, 2018)
تعالج هذه الدراسة موضوع التوافق النفسي لدى ذوى الاحتياجات الخاصة حيث تكمن مشكلة هذه الشريحة من المجتمع، في الظروف النفسية والاجتماعية المختلفة، والتي تضع قيودا وعقبات غير مبرره، ولا تستند إلى دراسات علمية أمام مشاركتهم في الحياة الاجتماعية. وتشير العديد من الدراسات والأبحاث إلى أن المشكلات التي تواجه ذوي الاحتياجات الخاصة في حياتهم التوافقية مع أنفسهم لا ترجع إلى الإصابة أو النقص الذي يعانون منه في حد ذاته، بل تعود حسب نتائج الدراسات إلي تلك الطريقة التي ينظر بها المجتمع إليهم. ونسعى من خلال هذه الدارسة إلى التعرف على مستوى التوافق النفسي لدى هذه الفئة من المجتمع، ومعرفة الفروق في درجة التوافق النفسي بین التلامیذ ذوي الاحتیاجات الخاصة باختلاف متغیر الجنس. The purpose of this study is to address the issue of psychological compatibility among people with special needs by identifying the level of psychological compatibility and detecting the possible differences in sex depending on the descriptive approach for being suitable with the subject of the study. A tool has been designed to measure this and after confirming its validity by measuring its psychometric characteristics ( the validity and reliability) which was applied on a sample of 30 students who attended primary school in the special departments in the city of Ouargla,- Algeria – was chosen randomly and the data were processed statistically using SPSS version 19; and the following results were obtained: The level of psychological compatibility among people with special needs is high; There are statistically significant differences in the level of psychological compatibility among people with special needs due to gender in favor of females. In view of the results reached, the following were suggested; The increase of interest in students with special needs in order to maintain this level of compatibility by building centers allocated to them; The need to build schools for the other educational stage, including students with special needs after graduation from rehabilitation centers.
مقال
Keywords: مستوى التوافق النفسي؛ ذوي الاحتياجات الخاصة; evel of psychological compatibility; people with special needs